Medicolegal Considerations with Intravenous Tissue Plasminogen Activator in Stroke: A Systematic Review - Archit Bhatt; Adnan Safdar; Dhara Chaudhari; Diane Clark; Amber Pollak; Arshad Majid; Mounzer Kassab (Stroke Research and Treatment)
Background. Intravenous tPA (tissue plasminogen activator) therapy remains underutilized in patients with Acute Ischemic Stroke (AIS). Anecdotal data indicates that physicians are increasingly liable for administering and for failure to administer tPA. Methods. An extensive search of Medline, Embase, Westlaw, LexisNexis Legal, and Google Scholar databases was performed. Case studies that involved malpractice litigation in ischemic stroke and thrombolytic therapy were analyzed systematically. Results. We identified 789 ischemic stroke litigation cases, of which 46 cases were related to intravenous tPA and stroke litigation. Case descriptions of 40 cases were available. Data for verdicts were available for 38 patients. The most frequent plaintiff claim was related to failure to administer intravenous tPA (38, 95%). Only 2 (5.0%) claim involved complications of treatment with tPA. Hospitals were defendants in majority of the 36 cases. Physicians were involved in 33 cases. While ED physicians were involved in 25 (60.52%) cases, neurologists were involved in 8 (20.0%) cases. There were 26 (65%) defendant-favored and 12 (30%) plaintiff-favored verdicts. Conclusion. Physicians and hospitals are at an increased risk of litigation in patients with AIS when in IV-tPA is being considered for treatment. While majority of the cases litigated were cases where tPA was not administered, only about 1 in 20 cases was litigated when complications occurred.